Open RAN: The technology, its politics and Europe's response - Hosuk Lee-Makiyama (European Centre for International Political Economy (ECIPE), 2020)
This policy brief explores the implications of Open RAN concept and its technical and political developments in the mobile network industry. Open RAN is not necessarily a new technology in itself, but represents a combination of existing technologies, e.g. virtualisation, AI, commercial off-the-shelf parts and open interfaces. Its proponents promise more secure networks without 'high-risk vendors' but Open RAN could introduce new systemic risks that must be addressed due to its reliance on open source software. While the proponents also promise significantly reduced costs, it is still inconclusive whether Open RAN in itself reduces the total costs of deploying a 5G network. Economic evidence shows that the equipment market is a buyers' market due to a higher concentration amongst operators. The number of vendors is less critical for prices than the relative power between buyers and sellers. The network equipment market is the only ICT segment where the EU manufacturers are still global leaders. If various industry consortiums call for subsidies, the EU has the commercial policy instruments to countervail against them. Some industry voices suggest that a certain Open RAN specification could replace existing global specifications under 3GPP. However, as today's market condition is not caused by the 3GPP standardisation, a solution is not to be found through developing alternative technical specifications. 3GPP is also more comprehensive than RAN. Thus, the question is whether Europe should try to sustain one common global umbrella of standards - or see the world balkanise into national or regional standards from 6G and onward. For better or worse, there will be regional fragmentation. The EU industrial policy could be facing a reality where network standards are politicised for commercial reasons - to pave way for an indigenous industry - which is unrelated to national security objectives. Also, EU operators may not react well if Open RAN open the door for cloud services to encroach into the telecom market. In conclusion, Open RAN has a raison d'etre as a promising new concept, even if it does not solve any geopolitical gambits. However, the EU have little to gain from government interventions in the RAN segment, which is just one element of the mobile network market.
Keywords: 330; Mobile Business; Telekommunikationsmarkt; Technischer Fortschritt; Industriepolitik; EU-Staaten